Retail investors' activity and climate disasters - FINTA, Marinela Adriana (Institutional Knowledge at Singapore Management University, 2024)
We analyze the effects of climate disasters on retail investors’ trading activity. Results show that retail investors trade significantly less during and around climate disasters, and retail buyers exhibit higher returns than sellers. Climate disasters weaken the positive return predictability of the past month’s order imbalances while strengthening it for the past six month’s order imbalances. In the short run, firms within climate disaster counties with retail net buying underperform those with negative imbalances. Instead, in the long run, firms within and outside climate disaster counties with positive order flows outperform those with negative order flows. Finally, the estimates on the return and order imbalance comovement around climate disasters are consistent with the main findings.